2020
DOI: 10.14245/ns.2040172.086
|View full text |Cite
|
Sign up to set email alerts
|

Full-Endoscopic Transcervical Ventral Decompression for Pathologies of Craniovertebral Junction: Case Series

Abstract: Odontoidectomy is very effective for the decompression of the ventral craniovertebral junction (CVJ). Various approaches are available for the direct ventral decompression of the CVJ. Because there are many disadvantages of open transoral approach, endoscopic odontoidectomy was developed. There are 3 approaches in endoscopic odontoidectomy. We report transcervical retropharyngeal endoscopic approach for the ventral CVJ in this paper. Three patients with different pathologies received operations using this appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
0
14
4
Order By: Relevance
“…Primarily, because these techniques necessitate a ventral approach, extended postoperative intubation is often required for these patients, which may contribute to the longer mean hospital stays. 35 For example, Husain et al found an average length of stay of 7 days, which is markedly longer than our reported aggregate length of stay of 4.5 days. 35 Postoperative dysphagia has also been a demonstrated complication, which has required the use of total parenteral nutrition or other means of nutritional supplementation.…”
Section: Discussioncontrasting
confidence: 72%
“…Primarily, because these techniques necessitate a ventral approach, extended postoperative intubation is often required for these patients, which may contribute to the longer mean hospital stays. 35 For example, Husain et al found an average length of stay of 7 days, which is markedly longer than our reported aggregate length of stay of 4.5 days. 35 Postoperative dysphagia has also been a demonstrated complication, which has required the use of total parenteral nutrition or other means of nutritional supplementation.…”
Section: Discussioncontrasting
confidence: 72%
“…Irreducible lesions require decompression at the side at which the compressions occur. The treatment algorithm was straightforward and convincing, which was supported by many published clinical series [ 2 , 7 , 23 , 26 - 33 ]. However, the surgical decision was always difficult because the reducibility was difficult to judge, especially for those patients in an acute stage.…”
Section: Discussionmentioning
confidence: 61%
“…The treatment algorithm was straightforward and convincing, which was supported by many published clinical series. 2,7,23,[26][27][28][29][30][31][32][33] However, the surgical decision was always difficult because the reducibility was difficult to judge, especially for those patients in an acute stage. Most patients in an acute stage were afraid of moving their head and neck due to severe neck pain and muscle spasm.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Yukoh Ohara et al also performed the similar procedure as us for odontoidectomy (14). Both of us used an "inside to outside" approach for odontoidectomy.…”
Section: Discussionmentioning
confidence: 99%